2018
DOI: 10.1029/2018sw001932
|View full text |Cite
|
Sign up to set email alerts
|

The 6 September 2017 X‐Class Solar Flares and Their Impacts on the Ionosphere, GNSS, and HF Radio Wave Propagation

Abstract: On 6 September 2017, the Sun emitted two significant solar flares (SFs). The first SF, classified X2.2, peaked at 09:10 UT. The second one, X9.3, which is the most intensive SF in the current solar cycle, peaked at 12:02 UT and was accompanied by solar radio emission. In this work, we study ionospheric response to the two X‐class SFs and their impact on the Global Navigation Satellite Systems and high‐frequency (HF) propagation. In the ionospheric absolute vertical total electron content (TEC), the X2.2 SF cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 46 publications
5
80
0
Order By: Relevance
“…Powerful solar flares can affect the ionosphere in the dayside regions of the Earth (Afraimovich et al, 2013). For instance, Yasyukevich et al (2018) reported significant flare effects during the 6-10 September interval in the Africa and Eurasia regions. These effects in general last less than the geomagnetic storm influence.…”
Section: Flare Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Powerful solar flares can affect the ionosphere in the dayside regions of the Earth (Afraimovich et al, 2013). For instance, Yasyukevich et al (2018) reported significant flare effects during the 6-10 September interval in the Africa and Eurasia regions. These effects in general last less than the geomagnetic storm influence.…”
Section: Flare Effectsmentioning
confidence: 99%
“…The authors also thank Ilya Zhivetiev from the Institute of Cosmophysical Research and Radio Wave Propagation FEB RAS and Yury Yasyukevich and Anna Mylnikova from the Institute of Solar-Terrestrial Physics SB RAS for providing TayAbsTEC software for this study (http://www.gnss-lab.org/tay-abs-tec; last access 30 June 2018). The dTEC calculations were performed with use of SIMuRG tool(Yasyukevich et al, 2018; https://simurg.iszf.irk.ru; last access: 28 June 2018). The GUVI/TIMED data were downloaded from http://guvitimed.jhuapl.edu (last access 26 August 2018).…”
mentioning
confidence: 99%
“…In this contribution, the analysis is performed for short baselines in atmosphere quiet days, so that the focus is on the multipath effects under different measurement scenarios. This leads to the second issue to be addressed in this contribution, i.e., determination of the overbounding mean and standard deviations for the between-receiver phase and code noise/biases under different measurement scenarios, which will be used for computation of the representative PLs during the IM.It is noted that during geophysical events like solar flare [22] and magnetic storms [23,24], abnormal ionosphere behaviours may lead to enlarged differential ionospheric errors in the RTK processing. Note that this study is focused on short-baseline RTK positioning in quiet atmosphere conditions, and does not attempt to account for the RTK integrity monitoring under extreme atmospheric conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The solar flare is an extreme space weather event, which can induce sudden increase in solar X-ray and extreme ultraviolet irradiance and cause many kinds of sudden ionospheric disturbances (Kumar et al, 2015;Liu et al, 2011;Xiong et al, 2014). Extensive studies have been carried out to investigate the solar flare effects on the ionosphere and the Global Navigation Satellite System (GNSS) applications (Le et al, 2013;Liu et al, 2011;Tsurutani et al, 2009;Wan & Yuan, 2005;Xiong et al, 2014;Xu et al, 2018;Yasyukevich et al, 2018). It can result in an increased measurement noise level and the loss of lock on GNSS signals (Chen et al, 2008;Jakowski et al, 1999).…”
Section: Introductionmentioning
confidence: 99%